Combined treatment with the histone deacetylase inhibitor LBH589 and a splice‐switch antisense oligonucleotide enhances SMN2 splicing and SMN expression in Spinal Muscular Atrophy cells. Issue 2 (8th January 2020) - Pagliarini, Vittoria; Guerra, Marika; Di Rosa, Valentina; Compagnucci, Claudia; Sette, Claudio
Abstract: Spinal muscular atrophy (SMA) is a motor neuron disease caused by loss of function mutations in the Survival Motor Neuron 1 ( SMN1 ) gene and reduced expression of the SMN protein, leading to spinal motor neuron death, muscle weakness and atrophy. Although humans harbour the highly homologous SMN2 gene, its defective splicing regulation yields a truncated and unstable SMN protein. The first therapy for SMA was recently approved by the Food and Drug Administration and consists of an antisense oligonucleotide ( Nusinersen ) rendering SMN2 functional and thus improving patients' motor activity and quality of life. Nevertheless, not all patients equally respond to this therapy and the long‐term tolerability and safety of Nusinersen are still unknown. Herein, in vivo splicing assays indicated that the HDAC inhibitor LBH589 is particularly efficient in rescuing the SMN2 splicing defect in SMA fibroblasts and SMA type‐I mice‐derived neural stem cells. Western blot analyses showed that LBH589 also causes a significant increase in SMN protein expression in SMA cells. Moreover chromatin immunoprecipitation analyses revealed that LBH589 treatment induces widespread H4 acetylation of the entire SMN2 locus and selectively favors the inclusion of the disease‐linked exon 7 in SMN2 mature mRNA. The combined treatment of SMA cells with sub‐optimal doses of LBH589 and of an antisense oligonucleotide that mimic Nusinersen (ASO_ISSN1) elicits additive effects on SMN2 splicing and SMN protein expression. These findings suggest that HDAC inhibitors can potentiate the activity of Nusinersen and support the notion that 'SMN‐plus' combinatorial therapeutic approaches might represent an enhanced opportunity in the scenario of SMA therapy. Abstract : Spinal muscular atrophy (SMA) is a motor neuron disease caused by loss of the Survival Motor Neuron 1 ( SMN1 ) gene and reduced expression of the SMN protein. Although humans harbour the highly homologous SMN2 gene, its defective splicing regulation makes it unable to compensate for the absence of SMN1 . The combined treatment of SMA cells with LBH589 (histone deacetylase inhibitor) and an antisense oligonucleotide that mimic Nusinersen (ASO_ISSN1) elicits additive effects on SMN2 splicing and SMN protein expression. These findings support the notion that "SMN‐plus" combinatorial therapeutic approaches might represent an enhanced opportunity in the scenario of SMA therapy.